gw-prime submodules - Bilgin, Zehra; Oral, Kursat Hakan; Tekir, Unsal (NATL UNIV COLOMBIA, DEPT MATHEMATICS, FAC SCIENCES, 2017)
In this work, gw-prime submodules of a module over a commutative ring with identity are defined. This class of submodules is a generalization of weakly prime submodules. After examining general properties of gw-prime submodules, their relation with valuation modules are investigated.
Keywords: gw-modules; gw-submodules; weakly prime submodules; valuation modules; valuation rings; Mathematics